An exploration of the parameters of liveable urbanism through inclusive incremental development - Duke, David (Department of Civil Engineering, 2020)
“Despite a significant reduction in the percentage of population living in informal settlements from 2000 to 2014, the absolute number of people living in deplorable conditions has increased from 689 to 880 million people over the same period. Current policy and planning practice in developing countries has not been able to cope with such pervasive rapid urbanisation. By 2050 the United Nations predicts two-thirds of the global population will live in cities. Of which as many as one-third of this population could be living in informal settlements (slums). To address these unsustainable and undesirable trends in support of the disadvantaged and maintaining environmental sustainability, this minor dissertation conducts comprehensive research of contemporary policy and planning work to seek alternatives. The purpose of the literature review is to identify commonalities, differences, gaps of knowledge and constraints of current policies and planning practice currently used to plan and manage growth of cities. Analysis and findings then inform and add value in exploring parameters for a 'liveable’ or improved urbanism from that currently experienced in informal settlements. Historic global policies focusing on government led top down approaches to provide large scale low cost housing have not kept up with demand, although they remain popular politically. From these policy and planning failures, it is evident that a more inclusive and incremental approach better utilizing available human capital should be considered. Critical analysis of literature with an alternative urbanism and planning paradigm in mind emerges in the findings and conclusion in the form of recommended parameters for a new inclusive and incremental urbanism. Such urbanism is entirely possible provided the critical issues identified such as lack of political will and good governance can be mitigated. To dramatically improve the lives of millions will require a compelling vision and collaborative effort seldom seen in current policy and planning of developing countries. Despite the daunting task, this paper seeks to define a conceptual framework drawn from findings to mitigate issues and guide an alternative vision of the future. The alternative urbanism that emerges from the conceptual framework may fall somewhere between that of current informal settlements and current discourse such as smart cities’’